Analysis Of Knowledge Of Women Aged (15-49 Years) About Personal Hygien And The Incident Of Vucility In The Krian Health Center Area Sidoarjo - Siti Julaichah; Riza Tsalatsatul Mufida; Erma Retnaningtyas; Miftakhur Rohmah (Journal of Health Science Community, 2024)
The high rate of vaginal discharge in the Krian Sidoarjo Community Health Center area is because many women of childbearing age do not know about vaginal discharge so they consider vaginal discharge as something normal and trivial. In addition, the feeling of shame when women experience vaginal discharge often makes these women reluctant to consult a doctor. This research aims to analyze the knowledge of women aged 15-49 years about personal hygiene and the incidence of vaginal discharge in the Krian Sidoarjo Community Health Center area. Research uses analytical methods with a cross sectional approach . The sample used a sampling technique with a stratified random sampling method, namely 98 samples from a total population of women of childbearing age (15-49 years) of 4870 people. This research uses a questionnaire instrument and data analysis uses the Chi Square test. The research results based on the Chi Square test show that the statistical test results obtained a sig (2-tailed) value of 0.001, which indicates that the value is smaller than 0.05 so that the p value is < α (0.05), so H1 is accepted. From this research there is a relationship between the knowledge of women aged 15-49 years about personal hygiene and the incidence of vaginal discharge in the Krian Sidoarjo health center area .